Association between Toll-Like Receptor 4 and Occurrence of Type 2 Diabetes Mellitus Susceptible to Pulmonary Tuberculosis in Northeast China - Yuze Li; Dianzhong Li; Jinfeng Zhang; Shurui Liu; Haijun Chen; Kun Wu (Stem Cells International)
The purpose of this study is to explore why type 2 diabetes mellitus (T2DM) patients are susceptible to pulmonary tuberculosis through detection of serum Toll-like receptor 4 (TLR4), an important immune-related receptor, especially in terms of content and TLR4 gene polymorphism. Patients with T2DM complicated by pulmonary tuberculosis (T2DMTB) were selected as the case group and T2DM patients without tuberculosis were selected as the control group. Forty patients in each group were randomly selected and their serum TLR4 levels were detected and compared. Determination of six sites of TLR4 gene polymorphism was carried out in 238 T2DMTB patients and 310 patients with T2DM, and results showed that the serum TLR4 content of the T2DMTB group was significantly lower than that of the T2DM group (p<0.05). The six sites of TLR4 gene polymorphism did not show significant associations with T2DMTB risk. No statistically significant differences in genotype distributions were observed between T2DMTB patients and patients with T2DM when studied using the recessive and dominant genetic models. How two diseases with contradictory nutritional statuses can occur in the same person is difficult to explain from environmental factors perspective alone. Future research should study the causes of T2DMTB from the perspective of genetics.